2021
DOI: 10.1002/ghg.2060
|View full text |Cite
|
Sign up to set email alerts
|

A low‐carbon strategy using INVELOX turbines in the presence of real‐time energy price uncertainty

Abstract: This paper provides innovation in wind turbine (WT) technology and its advantages in microgrid planning. The microgrid in this work includes various renewable and nonrenewable resources. The proposed low‐carbon strategy is implemented via two scenarios. In the first scenario, the uncertainty of selling and buying real‐time energy prices is investigated with and without the standard and portable (increased velocity) INVELOX turbines. In the second scenario, the authors study the operation of the microgrid assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The production of power from wind turbines relies on several factors, including wind speed, wind direction, turbine positioning, size, and the generator's dynamic performance. On the other hand, the output power of photovoltaic systems is influenced by the cell temperature and the level of solar radiation [34].…”
Section: Mathematical Modelling Of Systemmentioning
confidence: 99%
“…The production of power from wind turbines relies on several factors, including wind speed, wind direction, turbine positioning, size, and the generator's dynamic performance. On the other hand, the output power of photovoltaic systems is influenced by the cell temperature and the level of solar radiation [34].…”
Section: Mathematical Modelling Of Systemmentioning
confidence: 99%
“…Numerical and experimental results in another study, [56], shows that despite not reaching a full wind omnidirectionality, 378-432% increase in energy production was utilized with an INVELOX system compared to a traditional one. It has been shown that the application of INVELOX turbines in microgrids can reduce the environmental pollution and total cost of microgrid considering the financial uncertainties [57].…”
Section: Invelox Wind Systemmentioning
confidence: 99%